Wpływ podcinania korzeni i nawożenia na cechy biometryczne dwuletnich sadzonek buka zwyczajnego (Fagus sylvatica L.) - Kasprzyk, Winicjusz; Jastrzębowski, Szymon (Leśne Prace Badawcze, 2016)
The aim of this study was to examine the effects of pruning the root system and different doses of nitrogen fertilization on the height and root collar diameter of 2-year-old beech seedlings ( Fagus sylvatica L.). This research was conducted in the forest nursery Muchów (Jawor Forest District, regional directorate of State Forests in Wrocław) and two different pruning treatments (no pruning and at 12 cm depth) and nitrogen fertilization doses (25 and 50 kg×ha -1 ) were applied. Results from an ANOVA showed statistically significant differences between the two pruning treatments ( p= 0.000) as well as for the interaction of both treatment factors ( p= 0.019). Root collar diameter correlated with seedling height, both of which were significantly different for the two pruning treatments (p=0.000). No statistically significant impact by the nitrogen fertilization doses on seedling height could be observed ( p= 0.125). To conclude, we found that it is reasonable to reduce the doses of nitrogen fertilization to half the recommended amount, 25 kg×ha-1, if the root system is not pruned during the second growth year. Seedlings that do receive pruning should be fertilized using the recommended nitrogen doses.